Meningkatkan Motivasi dan Hasil Belajar Peserta Didik dengan Mengoptimalkan Penerapan Pendekatan Saintifik Strategi Discovery Learning dan Metode Diskusi di SDN Model Mataram - Setiarini, Aries (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2016)
This study aimed to know implementing of scientific approach learning discovery strategy and discussion method in effort to improve motivation and Indonesian learning achievement, PPKN, Social at class VI-A students of SD Negeri Model Mataram. Significant of this study was fostering students to develop learning skills in Cognitive group and how to be socialized with their friends as long as learning process in the real class. And for the teachers it could improve approach and learning model with implementing scientific and learning discovery strategy in cooperative learning with discussion method. This study conducted in two cycles, activities in every cycle were planning, acting, observing and reflecting. The result in cycle II showed that result of teachers’ observation was 4,64, result of students’ observation had mean score (4,21). Then effect of improving learning motivation improved with mean score of students’ learning was (89,38). Means indicator of completeness (> 4,0) and learning achievement (> 75,00) was reached. Because indicator of completeness had been proved success so this study was stopped in cycle II.